Efektivitas Penggunaan QRIS Dalam Memfasilitasi Transaksi UMKM Perspektif Ekonomi Syariah - Ilfin Hamida; Hayatul Millah; Moh Abd Rahman (Forum Kerjasama Pendidikan Tinggi, 2026)
The development of digital technology has encouraged a shift in payment systems from cash-based transactions to non-cash transactions. Although the Quick Response Code Indonesian Standard (QRIS) has been widely implemented as a standardized digital payment system in Indonesia, its utilization among Micro, Small, and Medium Enterprises (MSMEs), particularly in rural areas, still faces various challenges that affect its effectiveness. This study aims to analyze the effectiveness of QRIS in facilitating non-cash transactions among MSMEs in Karangbong Village and to examine its compatibility with Islamic economic principles. This research employed a descriptive qualitative approach using observation and interview techniques involving ten MSME owners who use QRIS in Karangbong Village. The findings indicate that the use of QRIS provides convenience, efficiency, security, and speed in transactions, thereby supporting smoother business operations. However, its utilization has not yet been fully optimized due to low digital literacy, the persistence of cash-based transaction habits among the community, and limited technological understanding. From the perspective of Islamic economics, the use of QRIS is permissible because it functions as a payment instrument that does not contain elements of riba (usury), gharar (uncertainty), or maysir (gambling), and is in line with the principles of justice, transparency, public benefit (maslahah), and convenience in economic activities.